INSTITUTIONALIZATION OF THE MYANMAR GOVERNMENT’S ILLIBERAL PEACEBUILDING IN THE KAREN NATIONAL UNION (KNU) ARMED CONFLICT - Azzahra, Salsabilla; Fahadayna, Adhi Cahya (Universitas Padjadjaran, 2026)
This article examines the Myanmar government’s illiberal peacebuilding practices in addressing the ongoing conflict with the Karen ethnic group. Using qualitative descriptive methods and a literature review, the author analyzes the dynamics of the relationship between the state and the Karen ethnic group, examining how security strategies, co-optation, and discriminatory policies are employed to suppress resistance. Using Comparative Historical Analysis as its method, this article will discuss the issue of this conflict from 2015 to 2021. The study shows that the 2015 nationwide ceasefire agreement failed to achieve inclusive peace; the Myanmar government prioritized stability and territorial control through repressive actions, human rights violations, and the implementation of the “Four Cuts” military strategy. The practice of media censorship, journalism, and the dissemination of false information further strengthened the regime’s illiberal character. The author concludes that although this strategy temporarily reduced the intensity of open conflict, Myanmar successfully implemented illiberal peacebuilding procedurally but failed to achieve genuine justice and reconciliation for the Karen ethnic group. The conflict continues and is prone to escalation, demonstrating that a false peace without democracy and substantive justice will always be fragile in Myanmar.